2023
DOI: 10.3390/molecules28104009
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Chalcones and Its Derivatives: Review and In Silico Studies

Abstract: Chalcones are direct precursors in the biosynthesis of flavonoids. They have an α,β-unsaturated carbonyl system which gives them broad biological properties. Among the biological properties exerted by chalcones, their ability to suppress tumors stands out, in addition to their low toxicity. In this perspective, the present work explores the role of natural and synthetic chalcones and their anticancer activity in vitro reported in the last four years from 2019 to 2023. Moreover, we carried out a partial least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 114 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…A structure-activity relationship (SAR) was rationalized by analyzing the substituents effects and it revealed key differences between those evaluated hybrids 3 a-h (Figure 3 Thereon, different studies have been reported with coumarin and chalcone derivatives, showing the great potential of these two pharmacophores containing methoxy groups, highlighting the properties in different biological models, including colorectal cancer. [31,56] Besides, Alhakamy and colleagues [57] also reported the in vitro anticancer activity of different coumarinchalcone hybrids. They showed two active molecules with methoxy substituents at the 3', 5' positions of the aroyl rings, with IC 50 values in the range of 6.8 μM and 17.2 μM on breast cancer cells (MCF-7 and MDA-MB-231).…”
Section: Effect Of Chalcone-coumarin Hybrids On Cell Viabilitymentioning
confidence: 99%
“…A structure-activity relationship (SAR) was rationalized by analyzing the substituents effects and it revealed key differences between those evaluated hybrids 3 a-h (Figure 3 Thereon, different studies have been reported with coumarin and chalcone derivatives, showing the great potential of these two pharmacophores containing methoxy groups, highlighting the properties in different biological models, including colorectal cancer. [31,56] Besides, Alhakamy and colleagues [57] also reported the in vitro anticancer activity of different coumarinchalcone hybrids. They showed two active molecules with methoxy substituents at the 3', 5' positions of the aroyl rings, with IC 50 values in the range of 6.8 μM and 17.2 μM on breast cancer cells (MCF-7 and MDA-MB-231).…”
Section: Effect Of Chalcone-coumarin Hybrids On Cell Viabilitymentioning
confidence: 99%
“…These groups can interact with specific molecular targets within cancer cells, such as enzymes or receptors, and disrupt their normal function. For example, chalcones with hydroxyl groups have been found to inhibit key enzymes involved in cell proliferation, while those with methoxy groups have shown potent anti-angiogenic effects [ 23 ].…”
Section: Structures and Mechanism Of Action Of Chalconesmentioning
confidence: 99%
“…In this work, we investigated a combined structure of xanthone and chalcone because both skeletons showed remarkable anticancer activities [23,32]. Thirtyseven xanthone-chalcone derivatives have been designed (Table 1).…”
Section: Docking Of Xanthone-chalcone Derivativesmentioning
confidence: 99%
“…It means the chloro substituent enhanced the anticancer activity of xanthone up to 1.85× stronger [28]. On the other hand, chalcone is another anticancer candidate, in which the anticancer activity of chalcone strongly depends on the presence of the other functional groups such as fluoro, chloro, bromo, iodo, cyano, carboxylic acid, nitro, sulfonic acid, methyl, amino, hydroxy, and thiol [29][30][31][32]. As an example, chlorinated chalcones gave the IC 50 value in a range of 0.8-4.3 μM against MCF-7, HeLa, and WiDr cancer cells [33][34].…”
Section: ■ Introductionmentioning
confidence: 99%